2010
DOI: 10.1007/s11240-010-9777-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic fidelity among Agave tequilana plants propagated asexually via rhizomes versus in vitro culture

Abstract: Agave tequilana is a species of great economic importance for the Mexican society. Like most agaves, it can be propagated either sexually or asexually. However, plants originating from rhizomes are mainly used for commercial production. The aim of this study was to determine the genetic fidelity of plants that were obtained from the field and propagated from rhizomes and of those propagated by in vitro culture methods (somatic embryogenesis and proliferation of axillary buds). We used an inverse ISTR (sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 23 publications
(20 reference statements)
1
12
0
Order By: Relevance
“…Most plant transposable elements (TEs) are transcriptionally silent [45], they constitute a significant proportion of Agave genomes [28] and contribute to the creation of genetic diversity in many plants [46] including Agave [47,48]. We identified TE-like sequences in agaves (Methods) (Additional file 1: Table S8), the majority of which are derived from retrotransposons (Additional file 1: Table S8).…”
Section: Resultsmentioning
confidence: 99%
“…Most plant transposable elements (TEs) are transcriptionally silent [45], they constitute a significant proportion of Agave genomes [28] and contribute to the creation of genetic diversity in many plants [46] including Agave [47,48]. We identified TE-like sequences in agaves (Methods) (Additional file 1: Table S8), the majority of which are derived from retrotransposons (Additional file 1: Table S8).…”
Section: Resultsmentioning
confidence: 99%
“…However genetic studies are necessary to determine the somaclonal variation. Genomic changes have been reported in A. tequilana Weber not only in micropropagated plants, but also in those propagated through natural asexual processes (Torres- Morán et al 2010). Asexual genetic variability has also been reported in A. fourcroydes (Infante et al 2003) and A. cupreata Trel et Berger (Martínez-Palacios et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the stress occasioned by these conditions may produce gene mutations, epigenetic changes, and activation of transposable elements, leading to somaclonal variation [43] In agaves, genetic fidelity in plants generated by in vitro culture has been studied in A. fourcroydes [48] and A. tequilana [49] [50]. Using AFLP as a molecular marker, González et al fourcroydes, a value that is much lower than those found in this work (55.04% for K33 and 64.73% for K7).…”
Section: Genetic and Epigenetic Variation Within And Between The Clonmentioning
confidence: 99%